Health professionals exposure to mobbing in a medical school hospital - Nehir Turkmen, Sevgi; Ustun, Cagatay; Ozdemir, Cigdem; Akyol, Tugba; Poyraz Cokmus, Fikret (Annals of Medical Research, 2021)
None
Keywords: Mobbing; Workplace; Residents; Psychiatry Nurses.